2022
DOI: 10.31850/makes.v5i3.1832
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi, Sikap dan Tingkat Pengetahuan Siswa SMA 1 Padang Panjang Terhadap LGBT (Lesbian, Gay, Biseksual dan Transgender)

Abstract: Tercapainya maturasi seksual pada usia remaja akhir menunjukan dorongan seksual yang akan menstimulus remaja untuk memenuhi kebutuhan seksual nya, bahkan dapat melakukan hal yang tidak pantas apabila tidak tercapai sehingga remaja tersebut akan mengembangkan perilaku seksual yang menyimpang. Salah satu perilaku menyimpang yang mungkin terjadi adalah perilaku LBGT (lesbian, gay, biseksual, dan transgender. Tujuan penelitian ini adalah mengetahui sejauh mana tingkat pengetahuan dan persepsi remaja terhada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The same previous study also explained that more than half of the respondents had a negative perception of LGBT and considered it as deviant behavior (Kamila & Casmini, 2020). Other research results indicated that society's perception of LGBT considers it as deviating from the social values embraced by the community (Rinita Amelia, Melya Susanti, 2022).…”
Section: P-valuementioning
confidence: 68%
“…The same previous study also explained that more than half of the respondents had a negative perception of LGBT and considered it as deviant behavior (Kamila & Casmini, 2020). Other research results indicated that society's perception of LGBT considers it as deviating from the social values embraced by the community (Rinita Amelia, Melya Susanti, 2022).…”
Section: P-valuementioning
confidence: 68%
“…Because it could be, teenagers have a deviant sexual orientation, but are not aware of it because of a lack of knowledge about sexual education. 18 One of the factors that influence perception is the level of emotion. 19,20 According to researchers, this goes back to the problem of lack of knowledge about sexual education among adolescents.…”
Section: Discussionmentioning
confidence: 99%